As the world turns implications of global shifts in higher education for theory, research and practice - Allen, Walter R.; Teranishi, Robert T.; Bonous-Hammarth, Marguerite (Advances in education in diverse communities ;, 2012)
As the World Turns" examines two of the major problems confronting higher education in this modern world: access to higher education remains a persistent problem for disadvantaged students around the world; universities that are highly segregated by race, culture, language, nationality, or immigration status have lower achievement for disadvantaged students - who are also more often targets of discrimination. This volume compares discriminated, underrepresented and excluded groups in universities around the globe; identifying personal, group, institutional and societal factors related to persistent inequality. Through a consortium of international scholars, the chapters present studies on minority student experiences and achievement, asking whether and how universities: exhibit difference, diversity and inequality; integrate multiple social groups; encourage respect between diverse communities; and use diversity to enhance student learning. This volume demonstrates how diversity and equity help advance academic excellence in global higher education.